Implementation of experimental cellular (cellular-genetic) therapies on the example of eye diseases - Kapczuk, Patrycja; Rogulska, Karolina; Stangret, Anna; Mularczyk, Agata; Szczęśniak, Angelika; Topczewska, Katarzyna; Grzeszczak, Konrad (Journal of Education, Health and Sport, 2020)
The development of technology and a modern research approach in the 21st century has enabled access to new therapies in many fields of medicine and nanotechnology. Work on the use of cellular therapies is carried out in leading centers around the world. According to the "clinicaltraial.gov" service, it is estimated that there are about 5.5 thousand clinical trials using stem cells. The classification of stem cells is based on their potential to differentiate into other cells, tissues, organs or the whole organism. In cell therapy 3 groups of stem cells are used: Pluripotent Stem Cells (PSC), multipotent and unipotent, which have two common features: the ability to self-revalue, that is, to divide and to differentiate in many directions. To date, there are no objective, randomized clinical trials that would clearly determine the efficacy and safety of the cell therapy used in ophthalmic diseases. Hope is given by gene therapies such as the recently approved Luxturna™ gene therapy used in hereditary retinal degeneration caused by mutations in the RPE65 gene. Research is currently underway on experimental cell therapies to treat the following diseases of the optic system: glaucoma, retinopathy, age-related macular degeneration (AMD), optic nerve atrophy, retinal pigmentation (RP) and Stargardt’s disease. Stem cell-based medical therapies are a promising and rapidly developing method of innovative treatment, especially for conditions that were previously considered incurable. The use of experimental cellular gene therapies in diseases of the visual organ gives hope to both patients and scientists, but the age of regenerative medicine has yet to come.